Evaluation of the effect of disinfection of Cuba CT-115 grass explants with sodium hypochlorite. Technical note - Hernández Montesinos, A. R.; Palma Pérez, J. J.; Abreu Cruz, Amanda; Herrera Villafranca, Magaly; Herrera, R. S. (Cuban Journal of Agricultural Science, 2023)
In order to evaluate the effect of different concentrations of sodium hypochlorite (3 and 5%) on the disinfection of explants, apical cone of Cenchrus purpureus vc. Cuba CT-115, for its in vitro establishment an experiment was developed in Laboratorio de Biotecnología de la Facultad de Agronomía de la Universidad Agraria de La Habana. Two observations were made at four and eight days after sowing. The data were analyzed by Chi-square comparison proportions, for p < 0.05 and ComparPro 1.0. statistical package was applied. The analysis of proportion comparison of the studied variables at four and eight days did not have significant differences between the treatments with sodium hypochlorite at 3 and 5%. There was not contamination by fungi or bacteria in the two treatments studied at four days. Bacterial contamination occurred at eight days, but there were not differences between treatments. The explants disinfection of Cuba CT-115 can be performed with both concentrations of sodium hypochlorite, but it is recommended to disinfect apical cones of Cuba CT-115 with 3% sodium hypochlorite, which allows a saving of this substance during the procedure. It is suggested to study other concentrations of sodium hypochlorite and different immersion times. Key words: apex, contamination, Cenchrus purpureus, in vitro